Potential Anticarcinogenic Effects From Plasma of Older Adults After Exercise Training: An Exploratory Study - Peres, Alessandra; Branchini, Gisele; Marmett, Bruna; Nunes, Fernanda Bordignon; Romão, Pedro R.T.; Olean-Oliveira, Tiago; Minuzzi, Luciele; Cavalcante, Mateus; Elsner, Viviane; Lira, Fabio Santos; Dorneles, Gilson Pires (Frontiers in Physiology, 2022)
Aim: To evaluate the impact of exercise training plasma on in vitro prostate cancer cell viability and proliferation. Methods: PC3 prostate cancer cells were incubated with plasma obtained from young men with high and low physical fitness (PF) (High PF, n=5; Low PF, n=5) and with the plasma collected from institutionalized older adults (n=8) before and after multimodal exercise training. Cell viability and proliferation, mitochondria membrane polarization, reactive oxygen species (ROS) generation, and apoptosis were evaluated after the cell treatment with plasma. Systemic cytokines were evaluated in the plasma of institutionalized older adults submitted to exercise training protocol. Results: Plasma from High PF men lowers both cell viability and proliferation after incubation time. PC3 cells also presented lower cell viability and diminished rates of cell proliferation after the incubation with post-training plasma samples of the older adults. The incubation of PC3 cells with post-training plasma of older adults depolarized the mitochondrial membrane potential and increased mitochondrial reactive oxygen species production. Post-training plasma did not change apoptosis or necrosis rates in the PC-3 cell line. Multimodal exercise training increased the plasma levels of IL-2, IL-10, IFN-α, and FGF-1, and decreased TNF-α concentrations in institutionalized older adults. Conclusion: Adaptations in blood factors of institutionalized older adults may alter cell viability and proliferation by targeting mitochondrial ROS in a prostate cancer cell line.